EKSOTIKA AGROPOLITIKA - Ms. Hasdiana (SURYA SENI, 2008)
The Exotic of Agropolita. Custom ceremony of Gorontalo bride is not just a ritual procession which interesting, but also can create sacred atmosphere, so  that at the execution not only impressing the luxuriant and hilarious, but containsthe certain symbolic meaning as expression of message of lives for the routers generations and wide publics.Gorontalo is one of agrarian area in Indonesia. For sustaining of economic growth rate, Gorontalo most have rest on agricultural sectors. Realize this potency, hence government of Gorontalo Province targeting “Agropolitan Program” asdevelopment pillar. One of the pre-eminent commodities is corn. Agropolitan Program is able to increases corn production and productivity.  Temporarily, exploiting of corn is focused at the seed only, the stem and leaf applied for livestockfood mixture, while the husk only becomes garbage (read: waste). The corn husk if tilled with creative tapped will produce functional and non-functional masterpieces which loaded with esthetic nuance, and the symbolic  meaning. Even, can becomes pioneer in processing sector of the corn husk and mascot for Gorontalo.Manifestation of dressmaking masterpiece from this corn husks, is a moral responsibility and real contribution, as response to its problematic and dynamics.Visual materialization is crated in installation art which collaborated with fashion show. The beauty, potency of natural resources, and custom ceremony of Gorontalo bride becomes inspiration of creation of dressmaking and other visual artmasterpiece, and then entitled by “The Exotic of Agropolita”.Keywords: custom ceremony, corn husk, and modiﬁ cation of cloth.